1987
DOI: 10.1017/s0022215100101343
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the round window with special reference to cochlear implantation

Abstract: When the multi-channel cochlear implant electrode is inserted into the scala tympani through the round window the operation is best performed via a posterior tympanotomy. The view of the round window membrane, however, is incomplete because of its orientation and the fact that it has a conical shape. Nevertheless, a good view along the basal turn is obtained after the antero-inferior overhang of the round window niche and the crista fenestrae have been removed. It might be damaging to drill away the postero-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 11 publications
0
49
0
2
Order By: Relevance
“…We will subsequently refer to this region as the anteroinferior margin of the RWM. There is a discrepancy over the nomenclature of the bony area adjacent to this region; some authors have referred to it as the crista fenestra (10,12,14,17) or crista semilunaris (13); others use the term postis anterior (18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will subsequently refer to this region as the anteroinferior margin of the RWM. There is a discrepancy over the nomenclature of the bony area adjacent to this region; some authors have referred to it as the crista fenestra (10,12,14,17) or crista semilunaris (13); others use the term postis anterior (18).…”
Section: Resultsmentioning
confidence: 99%
“…These areas were selected as previous studies have suggested placing the cochleostomy either directly through the RWM or in the otic capsule anterior, inferior, or anteroinferior to the RWM (7)(8)(9)(10)(11)(12)(13)(14). Using Amira's landmark editor, six points were placed on the model to represent potential sites of cochleostomy, three points evenly distributed across the surface of the RWM, and three points in the adjacent otic capsule (see Table 1).…”
Section: Evaluating the Anatomical Relationships Between Structures Imentioning
confidence: 99%
See 1 more Smart Citation
“…Since we skeletonized the FN and CT, we did not use the intraoperative bony landmarks mentioned previously in the medical literature. A previous study investigated the position of the RW niche through posterior tympanotomy (14). Our study focused on the exposure of the RW niche and its variations.…”
Section: Discussionmentioning
confidence: 99%
“…Once these bony overhangs have been removed and the round window membrane is fully exposed, a sharp bony crest, the crista fenestra, is identified in the anteroinferior border of the niche [Franz et al, 1987;Atturo et al, 2014]. The membrane of the round window arises from the free edge of the crest.…”
mentioning
confidence: 99%